Pretreatment Posttraumatic Stress Disorder Symptom Network Metrics Predict the Strength of the Association Between Node Change and Network Change During Treatment. Issue 1 (25th July 2019) - Papini, Santiago; Rubin, Mikael; Telch, Michael J.; Smits, Jasper A. J.; Hien, Denise A.
Abstract: Network analysis has been increasingly applied in an effort to understand complex interactions among symptoms in posttraumatic stress disorder (PTSD). Although methods that initially focused on identifying central symptoms in cross‐sectional networks have been extended to longitudinal data that can reveal the relative roles of acute symptoms in the emergence of the PTSD syndrome, the association between network metrics and symptom change during treatment have yet to be explored in PTSD. To address this gap, we estimated pretreatment PTSD symptom networks in a sample of patients from a multisite clinical trial for women with full or subthreshold PTSD and substance use. We tested the hypothesis that node metrics calculated in the pretreatment network would be predictive of the strength of the association between a symptom's change and the change in the severity of all other symptoms through the course of treatment. A symptom node's strength and predictability in the pretreatment network were each strongly correlated with the association between that symptom's change and overall change across the symptom network, r (15) = .79, p < .001 and r (15) = .75, p < .001, respectively, whereas a symptom's mean severity at pretreatment was not, r (15) = .27, p = .292. These findings suggest that a node's centrality prior to treatment engagement is a predictor of its association with overall symptom change throughout the treatment process. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Las métricas de la red de síntomas de TEPT previas al tratamiento predicen la fuerza de la asociación entre el cambio de nodo y el cambio de red durante el tratamiento ANÁLISIS DE RED DEL TEPT EN UNA MUESTRA EN TRATAMIENTO El análisis de red ha aplicado cada vez más esfuerzo por comprender las interacciones complejas entre los síntomas del trastorno de estrés postraumático (TEPT). Aunque los métodos inicialmente se enfocaron en identificar síntomas centrales en redes transversales, se han extendido a datos longitudinales que pueden revelar los roles relativos de los síntomas agudos en la aparición del síndrome de TEPT, la asociación entre las métricas de la red y el cambio de síntomas durante el tratamiento aún no han sido explorados en el TEPT. Para abordar esta brecha, estimamos las redes de síntomas de TEPT antes del tratamiento en una muestra de pacientes de un ensayo clínico multisitio para mujeres con TEPT completo o subumbral y uso de sustancias. Probamos la hipótesis de que las métricas de nodo calculadas en la red de pretratamiento serían predictivas de la fuerza de la asociación entre el cambio de un síntoma y el cambio en la gravedad de todos los demás síntomas a lo largo del tratamiento. La fuerza y ​​la previsibilidad de un nodo de síntomas en la red de pretratamiento se correlacionaron fuertemente con la asociación entre el cambio de ese síntoma y el cambio general en la red de síntomas, r (15) = .79, p <.001 y r (15) = .75, p <.001, respectivamente, mientras que la gravedad media de un síntoma en el pretratamiento no lo fue, r (15) = .27, p = .292. Estos hallazgos sugieren que la centralidad de un nodo antes de la participación en el tratamiento es un predictor de su asociación con el cambio general de los síntomas a lo largo del proceso de tratamiento. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Pretreatment PTSD symptom network metrics predict the strength of the association between node change and network change during treatment Traditional Chinese 標題: 治療前的PTSD症狀網絡指標, 能預測治療期間交點改變和網絡改變的交係強度 撮要: 越來越多研究使用網絡分析法, 以理解創傷後壓力症(PTSD)症狀之間的複雜相互作用。起初專注用於橫斷網絡找出中心症狀的方法, 現在被延伸用於能反映急性症狀在PTSD疾病出現的相對角色的縱貫數據。然而, PTSD的網絡指標跟治療時的症狀改變之間的關係仍未被探討。為填補這個漏洞, 我們透過由有完整或次臨限PTSD及濫用藥物的女性組成的多場所臨床試驗樣本, 預測治療前的PTSD症狀網絡。我們驗證以下假設:在治療前網絡計算出的交點指標, 能預測出在治療期間, 一種症狀的改變跟其他所有症狀的嚴重度改變之間的關連強度。在治療前網絡裡, 一種症狀的交點強度和預測力分別都跟該症狀的改變跟症狀網絡的整體改變的關係有強勁關連 (分別為 r(15) = .79, p < .001 與 r(15) = .75, p < .001), 但一種症狀在治療前的嚴重度平均數卻無此強勁關連 (r(15) = .27, p = .292) 。結果反映, 在治療前, 一個交點的中心性乃其在治療期間跟整體症狀改變的關係的預測變量。 Simplified Chinese 标题: 治疗前的PTSD症状网络指标, 能预测治疗期间交点改变和网络改变的交系强度 撮要: 越来越多研究使用网络分析法, 以理解创伤后压力症(PTSD)症状之间的复杂相互作用。起初专注用于横断网络找出中心症状的方法, 现在被延伸用于能反映急性症状在PTSD疾病出现的相对角色的纵贯数据。然而, PTSD的网络指标跟治疗时的症状改变之间的关系仍未被探讨。为填补这个漏洞, 我们透过由有完整或次临限PTSD及滥用药物的女性组成的多场所临床试验样本, 预测治疗前的PTSD症状网络。我们验证以下假设:在治疗前网络计算出的交点指标, 能预测出在治疗期间, 一种症状的改变跟其他所有症状的严重度改变之间的关连强度。在治疗前网络里, 一种症状的交点强度和预测力分别都跟该症状的改变跟症状网络的整体改变的关系有强劲关连 (分别为 r(15) = .79, p < .001 与 r(15) = .75, p < .001), 但一种症状在治疗前的严重度平均数却无此强劲关连 (r(15) = .27, p = .292) 。结果反映, 在治疗前, 一个交点的中心性乃其在治疗期间跟整体症状改变的关系的预测变量。